ANALISIS KESULITAN SISWA MEMAHAMI MATA PELAJARAN EKONOMI DAN ALTERNATIF PEMECAHANNYA ( STUDI KASUS PADA SISWA KELAS X IPS 1 DI MAN 1 MALANG ) - Mega Prastika; Prih Hardinto (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2017)
This study departs from the problem of learning difficulties that leads to low learning outcomes. Solutions offered are students and teachers knowing the location of learning difficulties to find out the factors that cause it and then find an appropriate alternative. This research uses quantitative and qualitative approach. Quantitative data resulting from the results of diagnostic tests and qualitative data questionnaires results through in-depth observation and interviews. Checking the validity of data using source triangulation techniques. The results showed the percentage of student difficulties in clearing keyword with the total difficulty 96,30%. Cause students have difficulty using foreign term / terminology, lesson time and teaching methods of teachers. Efforts that have been made to overcome difficulties students to ask friends, browse and ask the teacher. While the efforts made by teachers by providing motivation and assistance during the learning activities took place. DOI: https://dx.doi.org/10.17977/UM014v10i22017p140